Polarization-Induced Transport: A Comparative Study of Ferroelectric and Non-Ferroelectric Dielectric-Gated Organic Field-Effect Transistors. (2nd May 2017) - Laudari, Amrit; Gangopadhyay, Shubhra; Guha, Suchismita
ABSTRACT: A comparative study of ferroelectric and non-ferroelectric-gated organic field-effect transistors (FETs) have been carried out by using a small molecule semiconductor 6, 13 bis(triisopropylsilylethynyl) pentacene (TIPS-pentacene) to understand the fundamental aspects of carrier transport in FET architectures. Temperature-dependent current-voltage characteristics from non-ferroelectric dielectric-gated FETs show a clear activated transport, independent of the dielectric constant. While using the ferroelectric dielectric polymer poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE), where the dielectric constant may be tuned by changing the temperature, a negative temperature coefficient of the carrier mobility is observed beyond 200 K. The polarization fluctuation dominant transport inherent to a ferroelectric dielectric in conjunction with the discrete nature of traps in TIPS-pentacene results in an effective de-trapping of the shallow trap states into more mobile states.